2023
DOI: 10.3390/antibiotics12030435
|View full text |Cite
|
Sign up to set email alerts
|

Non-Toxigenic Clostridioides difficile Strain E4 (NTCD-E4) Prevents Establishment of Primary C. difficile Infection by Epidemic PCR Ribotype 027 in an In Vitro Human Gut Model

Abstract: Clostridioides difficile infection (CDI) remains a significant healthcare burden. Non-toxigenic C. difficile (NTCD) strains have shown a benefit in preventing porcine enteritis and in human recurrent CDI. In this study, we evaluated the efficacy of metronidazole-resistant NTCD-E4 in preventing CDI facilitated by a range of antimicrobials in an in vitro human gut model. NTCD-E4 spores (at a dose of 107) were instilled 7 days before a clinical ribotype (RT) 027 (at the same dose) strain (210). In separate experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Moreover, direct competition with a non-toxic C. difficile strain (NTCD) can be used as preventive strategy of CDI. In vitro models of the human gut have shown that inoculation with an NTCD successfully prevents the development of CDI with the hypervirulent strain RT027 after the administration of a number of different antibiotics [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, direct competition with a non-toxic C. difficile strain (NTCD) can be used as preventive strategy of CDI. In vitro models of the human gut have shown that inoculation with an NTCD successfully prevents the development of CDI with the hypervirulent strain RT027 after the administration of a number of different antibiotics [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another method in the prevention of CDI is through direct competition with a nontoxigenic C. difficile strain (NTCD). In vitro models of the human gut have shown that prior inoculation with a NTCD strain successfully prevented the development of simulated CDI with the hypervirulent RT027 strain after administering a range of different antibiotics [ 54 ]. Recently, oral immunization of mice with spores from a genetically modified NTCD strain (NTCD_Tcd169) to target both C. difficile toxins and adhesion/colonization factors resulted in effective protection against hypervirulent strain RT027 R20291 and reduced excretion of R20291 spores when compared to treatment with NTCD strains [ 55 ].…”
Section: Next Generation Live Biotherapeuticsmentioning
confidence: 99%